PELATIHAN INVESTASI DI PASAR SAHAM KEPADA KOMUNITAS INVESTOR PEMULA: “FROM BEGINNER TO BE WINNER” - Lestari, Rohmini Indah; Indarto, Indarto (Fokus ABDIMAS, 2023)
The OJK program "Let's Save for Stocks" came into effect during the Covid-19 Pandemic, so that the number of new investors in the Indonesian stock market increased. This phenomenon is not being supported by an increase in knowledge and understanding of stock investment. The new investor behavior tends to be lazy to analyze to determine what stocks to trade and invest. The purpose of this community service is to provide training on procedures and strategies for investing in the stock market to novice investors. There will be an increase in the understanding and the ability of trading to obtain optimal returns. The PKM MM USM Lecturer Team collaborated with the IDX Representative Office in Central Java and PT. Panin Sekuritas Semarang provides material on investment strategies and stock trading, starting from understanding trading mechanisms, fundamental and technical analysis. The achievement of the activity objectives can be seen from the results of the pre-test and post-test. The increase in participants' understanding increased by 26.9% after receiving the training. This training has been sustainable through investment and trading assistance, questions and answers, and information sharing through the What's App group.Keywords: capital market,invesment, investor, stock, trading, training